Primary School Syllabus (Standards III, IV & V): Language Arts - Trinidad and Tobago. Ministry of Education (Ministry of Education, 1999)
This syllabus introduces a new approach to the teaching of Standard English, which reflects contemporary thinking about the nature and purpose of language, and the processes involved in language learning and their implications for language teaching. The new syllabus also takes account of the second language learning, and suggest some strategies that should be used in teaching a second language (Standard English) in the context of a first language (Trinidad Creole). This syllabus document, which is sequenced for Standards III, IV & V, contains the following elements in increasing levels of complexity with the spiral of the English language arts curriculum: Listening, Speaking, Visual Literacy, Literature, Reading –Mechanics, Vocabulary, Reading-Comprehension, Study Skills, Writing-Process/Mechanics, and Grammar. Each element is treated under the following headings: Component, Outcome/Objectives, Suggested Teaching Strategy, Sample Assessment/Evaluation, Connected Activity, and Resources.
GORTT/IBRD Basic Education Project
Keywords: Primary school curriculum